Paradoxical Association Between Baseline Apolipoprotein B and Prognosis in Coronary Artery Disease: A 36,460 Chinese Cohort Study - Li, Huanqiang; Wang, Bo; Mai, Ziling; Yu, Sijia; Zhou, Ziyou; Lu, Hongyu; Lai, Wenguang; Li, Qiang; Yang, Yongquan; Deng, Jingru; Tan, Ning; Chen, Jiyan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Apolipoprotein B (ApoB) and low-density lipoprotein cholesterol (LDL-C) were identified targets for blood lipid management among coronary artery disease (CAD) patients. Previous studies reported an inverse correlation between baseline LDL-C concentration and clinical outcomes. However, few studies explored the association between baseline ApoB and long-term prognosis. Methods: A total of 36,460 CAD patients admitted to Guangdong Provincial People's Hospital were enrolled and categorized into two groups: high ApoB (≥65 mg/dL) group and low ApoB (< 65 mg/dL) group. The association between baseline ApoB and long-term all-cause mortality was evaluated by the Kaplan-Meier method, Cox regression analyses and restricted cubic splines. Results: The overall mortality was 12.49% (n = 4,554) over a median follow-up period of 5.01 years. Patients with low baseline ApoB levels were paradoxically more likely to get a worse prognosis. There was no obvious difference in long-term all-cause mortality among ApoB patients when only adjusted for age, gender, and comorbidity (aHR: 1.07, 95% CI: 0.99-1.16). When CONUT and total bilirubin were adjusted, the risk of long-term all-cause mortality would reduce in the low-ApoB (< 65mg/dL) group (aHR: 0.86, 95% CI: 0.78-0.96). In the fully covariable-adjusted model, patients in the ApoB<65mg/d group had a 10.00% lower risk of long-term all-cause mortality comparing to patients with ApoB≥65mg/dL (aHR: 0.90; 95% CI:0.81-0.99). Conclusion: This study found a paradoxical association between baseline ApoB and long-term all-cause mortality. Malnutrition and bilirubin mainly mediate the ApoB paradox. Increased ApoB concentration remained linearly associated with an increased risk of long-term all-cause mortality.